INFLUENCE OF INSTITUTIONAL CHARACTERISTICS ON COMPETITIVENESS OF PRIVATE UNIVERSITIES IN NAIROBI COUNTY, KENYA - Nderitu, Nene; Edabu, Dr. Paul; Chui, Dr. Mary Mugwe (African Journal of Education and Practice, 2020)
Purpose: In the last three decades, the republic of Kenya has witnessed a tremendous increase in the number of chartered universities and a stiff competition for students. The student enrolment base coupled with the emergence of private university education providers turned the university arena in Kenya into a student enrolment market, leading to intense competition between Public and Private Universities. The researcher realizes that, the existing studies relate competitiveness to performance. Thus, the purpose of this study was to assess the influence of institutional characteristics as a planning strategy on competitiveness of private universities in Nairobi County, Kenya. Resource Based Theory, Competitive Advantage Theory and Generic Framework Theory guided this study. Methodology: The study applied mixed method approach and thus adopted concurrent triangulation design. Target population comprised 66 Registrar Academics, 66 Registrar Admissions and 33 Directors of Marketing all totalling to 165. Using the Central Limit Theorem, 36 Registrars of Academics, 36 Registrars of Admissions and 18 Directors of Marketing were purposively sampled. Questionnaires were used to collect data from Registrar Academic and Admissions whereas interview guide was used to gather data from the Directors of Marketing. Data analysis began by identifying common themes from the respondents' description of their experiences. Qualitative data were analyzed thematically along the objectives and were presented in narrative forms. Quantitative data were analyzed using descriptive statistics and inferential using Chi-Square through Statistical Packages for Social Science and presented using tables. Findings: The study established that institutional characteristics as a planning strategy influence competitiveness of private universities. These include inclusivity, size and leadership styles which have improved enrollment of students in undergraduate and postgraduate programmes. Unique Contribution to Theory, Policy and Practice: The study recommends that, in order to enroll more students, universities should have a sizable management which involves all stakeholders.